2012
DOI: 10.1016/j.jsbmb.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid inhibits aromatase activity and phosphorylation: Potential mechanism for additive zoledronic acid and letrozole drug interaction

Abstract: Zoledronic acid (ZA), a bisphosphonate originally indicated for use in osteoporosis, has been reported to exert a direct effect on breast cancer cells, although the mechanism of this effect is currently unknown. Data from the ABCSG-12 and ZO-FAST clinical trials suggest that treatment with the combination of ZA and aromatase inhibitors (AI) result in increased disease free survival in breast cancer patients over AI alone. To determine whether the mechanism of this combination involved inhibition of aromatase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Whole cell lysates were prepared as previously described (19). For cell fractionation, cells were scraped by rubber policeman in dPBS, washed twice, and centrifuged at 1000 rpm for 5 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole cell lysates were prepared as previously described (19). For cell fractionation, cells were scraped by rubber policeman in dPBS, washed twice, and centrifuged at 1000 rpm for 5 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…mRNA and promoter expression were measured using qPCR as previously described (19). PCR reactions were amplified for 50 cycles with an annealing temperature of 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…AC1 cells are another set of MCF-7 cells stably transfected with the human placental aromatase gene [ 37 ]. Similar to MCF-7Ca cells, AC1 cells are ER+/HER2-, proliferate in response to estrogen or androstenedione, express the aromatase enzyme and are sensitive to aromatase inhibitors [ 38 ]. AC1 cells, however, were created in our laboratory rather than Dr. Chen’s, and they express higher levels of aromatase (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…It was previously shown that zoledronate prevented deep bone loss when goserelin was combined with tamoxifen or anastrozole [5]. In a similar study, Schech et al [6] showed that the combination of letrozole and zoledronate caused increased inhibition of aromatase activity compared with letrozole alone. Zoledronate can inhibit the aromatase enzyme by inhibition of serine phosphorylation.…”
mentioning
confidence: 91%